Cardiac G-protein-coupled receptor kinase 2 ablation induces a novel Ca2+ handling phenotype resistant to adverse alterations and remodeling after myocardial infarction - Raake, Philip; Most, Patrick; Katus, Hugo (Circulation, 2012)
Background—G-protein-coupled receptor kinase 2 (GRK2) is a primary regulator of β-adrenergic signaling in the heart. G-protein-coupled receptor kinase 2 ablation impedes heart failure development, but elucidation of the cellular mechanisms has not been achieved, and such elucidation is the aim of this study.Methods and Results—Myocyte contractility, Ca2+ handling and excitation-contraction coupling were studied in isolated cardiomyocytes from wild-type and GRK2 knockout (GRK2KO) mice without (sham) or with myocardial infarction (MI). In cardiac myocytes isolated from unstressed wild-type and GRK2KO hearts, myocyte contractions and Ca2+ transients were similar, but GRK2KO myocytes had lower sarcoplasmic reticulum (SR) Ca2+ content because of increased sodium-Ca2+ exchanger activity and inhibited SR Ca2+ ATPase by local protein kinase A-mediated activation of phosphodiesterase 4 resulting in hypophosphorylated phospholamban. This Ca2+ handling phenotype is explained by a higher fractional SR Ca2+ release induced by increased L-type Ca2+ channel currents. After β-adrenergic stimulation, GRK2KO myocytes revealed significant increases in contractility and Ca2+ transients, which were not mediated through cardiac L-type Ca2+ channels but through an increased SR Ca2+. Interestingly, post-MI GRK2KO mice showed better cardiac function than post-MI control mice, which is explained by an improved Ca2+ handling phenotype. The SR Ca2+ content was better maintained in post-MI GRK2KO myocytes than in post-MI control myocytes because of better-maintained L-type Ca2+ channel current density and no increase in sodium-Ca2+ exchanger in GRK2KO myocytes. An L-type Ca2+ channel blocker, verapamil, reversed some beneficial effects of GRK2KO.Conclusions—These data argue for novel differential regulation of L-type Ca2+ channel currents and SR load by GRK2. G-protein-coupled receptor kinase 2 ablation represents a novel beneficial Ca2+ handling phenotype resisting adverse remodeling after MI.